2000
DOI: 10.1137/s0036139999360696
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Noise Stabilizes Periodic Wave Patterns in Oscillatory Systems on Finite Domains

Abstract: Invasions in oscillatory systems generate in their wake spatiotemporal oscillations, consisting of either periodic wavetrains or irregular oscillations that appear to be spatiotemporal chaos. We have shown previously that when a finite domain, with zero-flux boundary conditions, has been fully invaded, the spatiotemporal oscillations persist in the irregular case, but die out in a systematic way for periodic traveling waves. In this paper, we consider the effect of environmental inhomogeneities on this persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Particularly, spiral patterns are being investigated theoretically in a number of reaction-diffusion predator-prey systems, such as Holling-type model (Savill & Hogeweg, 1999;Malchow et al, 2000), Ivlev-type (Sherratt, Lewis & Fowler, 1995;Sherratt, Eagan & Lewis, 1997;Kay & Sherratt, 2000;Pearce et al, 2006;Garvie, 2007;Preedy et al, 2006;Uriu & Iwasa, 2007), and so on. The functional responses of these predatorprey models are all prey-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, spiral patterns are being investigated theoretically in a number of reaction-diffusion predator-prey systems, such as Holling-type model (Savill & Hogeweg, 1999;Malchow et al, 2000), Ivlev-type (Sherratt, Lewis & Fowler, 1995;Sherratt, Eagan & Lewis, 1997;Kay & Sherratt, 2000;Pearce et al, 2006;Garvie, 2007;Preedy et al, 2006;Uriu & Iwasa, 2007), and so on. The functional responses of these predatorprey models are all prey-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…where α = Both ecologists and mathematicians are interested in the Ivlev-type predatorprey model and much progress has been seen in the study of model (3) (May, 1981;Metz & Diekmann, 1986;Kooij, 1996;Sugie, 1998;Tian, 2006;Preedy et al, 2006) and model (4) (Sherratt, Lewis & Fowler, 1995;Sherratt, Eagan & Lewis, 1997;Kay & Sherratt, 2000;Pearce et al, 2006;Garvie, 2007;Preedy et al, 2006;Uriu & Iwasa, 2007). The results indicate that the Ivlev-type predator-prey model (3) and (4) have widely applicabilities in ecology, such as dynamics in predator-prey system (May, 1981;Metz & Diekmann, 1986;Sherratt, Lewis & Fowler, 1995;Sherratt, Eagan & Lewis, 1997;Tian, 2006), host-parasitoid system (Pearce et al, 2006;Preedy et al, 2006), fish skin pattern (Uriu & Iwasa, 2007), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, the simple form of this periodic wave family has provided an invaluable reference point for the study of periodic travelling waves in more general reaction-diffusion systems. This work has focussed in particular on the existence and stability of periodic travelling waves (Ermentrout, 1981;Maginu, 1979Maginu, , 1981Kapitula, 1994), other cases with exact solutions (Cope, 1979;Romero et al, 2000) and the generation of periodic travelling waves by environmental heterogeneities (Auchmuty & Nicolis, 1976;Hagan, 1981;Kopell, 1981;Kay & Sherratt, 2000;Sherratt, 2003) and behind invasive wavefronts (Sherratt, 1994(Sherratt, , 1996Ermentrout et al, 1997;Petrovskii et al, 1998;Petrovskii & Malchow, 2000, 2001Webb & Sherratt, 2004;Garvie, 2007).…”
Section: λ λ λ-ω ω ω Systemsmentioning
confidence: 99%
“…These may have the form of noise in parameter values (Hagan, 1981;Kopell, 1981;Kay & Sherratt, 2000) or forcing applied at a boundary of the domain. Both mechanisms have been studied extensively for chains of coupled oscillators (Ermentrout & Kopell, 1984, 1986Kopell et al, 1991;Ren & Ermentrout, 1998), but in oscillatory reaction-diffusion equations, there has been very little work on boundary-driven periodic travelling 760 J.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples include PTWs and patterns of regional synchrony in geometrid moths in Northern Fennoscandia [5][6][7][8][9], PTWs and intermittent synchrony in red grouse [10,11], and PTWs in larch budmoth in the European Alps [12][13][14]; see Sherratt & Smith [15] for further examples. Modelling studies have demonstrated a number of potential causes for this spatial asynchrony, including invasions [16][17][18][19][20][21], heterogeneous habitats [13,[22][23][24], migration between subpopulations [25], migration driven by pursuit and evasion [26] and hostile habitat boundaries [27][28][29][30]. This paper concerns the last of these.…”
Section: Introductionmentioning
confidence: 99%